2017
DOI: 10.1161/strokeaha.116.015900
|View full text |Cite
|
Sign up to set email alerts
|

Do Women With Atrial Fibrillation Experience More Severe Strokes?

Abstract: Women with AF do not only have an increased risk of stroke when compared with men but also experience more severe strokes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 13 publications
1
39
0
1
Order By: Relevance
“…Despite the availability of adequate therapy, AF-related strokes are still estimated to cost US$ 8 billion annually in the USA29 30 or over 9000 GBP per stroke in the UK 31. The increased severity of AF-related strokes compared with other aetiologies32 may even increase the negative effect of general embolic events on quality of life 33. As a consequence, it is urgently necessary to ameliorate adherence to OAC therapy for AF.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of adequate therapy, AF-related strokes are still estimated to cost US$ 8 billion annually in the USA29 30 or over 9000 GBP per stroke in the UK 31. The increased severity of AF-related strokes compared with other aetiologies32 may even increase the negative effect of general embolic events on quality of life 33. As a consequence, it is urgently necessary to ameliorate adherence to OAC therapy for AF.…”
Section: Discussionmentioning
confidence: 99%
“…Women exhibit lower rates of stroke at premenopausal ages than male counterparts, but higher rates of stroke later in life (19,37). Furthermore, women experience more severe strokes, as well as higher rates of disability and mortality (3); while these differences are partially attributed to the fact that women are typically older at stroke onset (37), several studies have reported these trends independently of age (13,28,40), and similar sex-associated effects have been observed in animal models (19,43).…”
mentioning
confidence: 83%
“…Biologically, the mechanisms that drive these sex differences are not yet fully understood. While it is believed that these differences are at least in part driven by the direct physiological effects of estrogen (25), the fact that several sex differences persist following menopause (13,28,40) and independently of estrogen status (15) suggests additional mechanisms that have yet to be elucidated. Better characterization of these mechanisms has the potential to provide valuable insights into the molecular mediators that modify stroke risk and influence outcome.…”
mentioning
confidence: 99%
“…Before simple and multiple linear regression analyses, admission hematoma volume was cube root transformed for each patient to satisfy statistical assumptions about normality of distribution 20. Similarly, admission NIHSS scores were square transformed for each patient to satisfy statistical assumptions about normality of distribution 21. In all univariable analyses, a threshold of P <0.1 was used to identify candidate variables for inclusion in multiple linear regression models that tested statistical significance hypothesis with an α value of 0.05 22.…”
Section: Methodsmentioning
confidence: 99%